Człowiek a prawda. Paremiczne ukształtowanie odniesień (Conversatoria Linguistica, 2022)
The description of the category of truth in the light of linguistic material is characterized by its reference to man. The analysis of the Polish paremies against the background of other Slavic languages reveals a two-way relationship: truth in relation to man and man in relation to truth. It allows for the reconstruction of: in connection with man; being in harmony with the truth and being inconsistent with the truth in the dimension of correlating a person with the truth.